Probióticos de culturas definidas e indefinidas no controle de Salmonella Enteritidis em frangos de corte - Carvalho, Erich Helfer (2012)
A global public health concern are diseases transmitted by food. Salmonellosis as the second figure of foodborne disease more common in countries like United States, Canada and the European Community. In Brazil since 1999 until 2011 the Salmonella bacterium is the leading cause of foodborne illness. Salmonella is a gram-negative, non-spore-forming and due to biochemical differences are divided into two species: Salmonella bongori and Salmonella enterica and the last divided into six subspecies: enterica, salamae, arizonae, diarizonae, houtenae and indica. The Salmonella enterica enterica serovar Enteritidis is a major serotypes found in birds that are related to Salmonellosis in humans. In recent decades the main way to control bacterial diseases in poultry farms was the use of antimicrobials. However, the use of these drugs as a preventive measure has been questioned since extensive reports have appeared on the antimicrobial resistance among pathogenic bacteria. Thus, the prohibition of various antibiotics in poultry has raised the need to develop new ways to control bacterial infections and improves on the performance. Probiotics have been proposed as candidates to fill this gap. Probiotics have been defined as live microorganisms comprise additives which, when administered in adequate amounts, confer health benefits modulating the host's immune system. Probiotics may be constituted by cultures of microorganisms defined or undefined cultures of microorganisms. However, there are no studies to prove which of the constitutions of probiotics is most effective in controlling Salmonella, which requires further study in relation to the different constitutions of probiotics available for use. In this context, the objective of this study is to address through a literature review on the importance of public health Salmonella and probiotics as relevant control tool Salmonellosis. A second goal is to develop a chapter with an article titled: "Efficacy of a Probiotics Cultures Defined and Undefined in Control of Salmonella Enteritidis in Broilers".